Reproductive Schedule of the Silver Shiner (Notropis photogenis) in the Flint River of Alabama - Kelly Hodgskins; Stephanie Greenleaf; Jonathan Hillman; Bruce Stallsmith (Southeastern Fishes Council Proceedings, 2016)
Many river-dwelling species of fish are dependent upon and stimulated by fluctuations in river flow for successful reproduction. This is especially true of pelagophils, a reproductive guild whose eggs and larvae require free drifting on river currents for several days. Notropis photogenis (Silver Shiner) is a rheophilic species with a broad distribution from Ontario to the southeastern United States including northern tributaries to the Tennessee River in Alabama. Little is known of its reproductive biology. The purpose of this study was to describe aspects of reproductive biology such as timing and pattern of ovarian development and oocyte maturation of N. photogenis in the Flint River of Alabama. We investigated whether and how abiotic cues such as river discharge and temperatures were related to ovulation and spawning. Monthly fish collections were made from August, 2011, to July, 2013. From these collections monthly gonadosomatic index (GSI) was evaluated, along with the status of ovarian maturation, oocyte maturation and size, and oocyte counts to establish fecundity and clutch size. Median monthly river discharges in cubic feet per second for 1999–2015 were obtained from the U.S. Geological Survey database. Observations over two years showed associations between daily mean discharge and months of peak GSI (February–April). Mean GSI peaked in March of both 2012 and 2013 when median flow was approximately 600 cfs. Large synchronous spawning events appear to occur during times of steady substantial discharge increases but after peaks of discharge > 3000 cfs.
Keywords: cyprinid; freshwater ecology; synchronous spawning